FREQUENCY OF EXTENDED SPECTRUM BETA LACTAMASE PRODUCING GRAM NEGATIVE BACILLI AMONG CLINICAL ISOLATES AT CLINICAL LABORATORIES OF ARMY MEDICAL COLLEGE, RAWALPINDI - Ali, AM; Rafi, S; Qureshi, AH (Journal of Ayub Medical College Abbottabad, 2004)
Background: This study was carried out in Microbiology department of Army Medical College, Rawalpindi to find out the frequency of extended spectrum beta lactamase producing gram negative bacilli among clinical isolates recovered from clinical specimens received from Military Hospital, Rawalpindi. Methods: This study was carried out from 1st Jan 2002 to 30th Dec 2002. A total of 812 consecutive Gram-negative bacilli were recovered during the study period from various samples including urine, blood, pus, sputum, high vaginal swab (HVS), aspirates, i/v canula/ Central venous lines (CVP), chest tubes and catheter tips. Extended spectrum beta lactamase detection in these isolates was carried out by Kirby Bauer disc diffusion method on Mueller Hinton agar. A susceptibility disk containing amoxicillin-clavulanate was placed as the inhibitor of beta lactamase in the center of the plate, and cefotaxime, ceftazidime, ceftriaxone and aztreonam disks were placed 30 mm (center to center) from the amoxicillin-clavulanate disk. Enhancement of the zone of inhibition of the oxyimino–lactam caused by the synergy of the clavulanate in the amoxicillin-clavulanate disk was considered as evidence of ESBL production. Escherichia coli ATCC 25922 and K. pneumoniae ATCC 700603 were used as control strains. Results: The frequency of ESBL producing gram negative bacilli among the clinical isolates was 45%. Keywords: ESBL. Antibiotic. Nosocomial. Enterobacteriaceae